THE EFFECT OF ONLINE CUSTOMER REVIEW COMMUNICATION ON PURCHASE INTEREST WITH TRUST AS INTERVENING IN BUKALAPAK ONLINE STORE IN PADANG CITY - Zike Martha; Asni Dewi Syahriani Bishry; Defhany (JOSAR (Journal of Students Academic Research), 2022)
This research is choosing a topic to determine the effect of online customer review communication on purchase interest with trust as an intervening at the Bukalapak online store in the city of Padang. The population in this study were all consumers who shopped online at the Bukalapak online store in Padang City in 2020 whose number was not known with certainty, with a total sample of 138 people. The sampling technique used nonprobability sampling method with accidental sampling technique. The data analysis method used partial least squares (PLS). The summary of the results obtained from this study shows that online customer reviews have a significant positive effect on consumer trust in the online shop Bukalapak in the city of Padang. Online customer reviews have a significant positive effect on consumer purchase interest at Bukalapak online store in Padang City. Trust has a significant positive effect on consumer purchase interest at Bukalapak online store in Padang City. Then online customer reviews have a significant positive effect on purchase interest through trust in the online shop Bukalapak in the city of Padang.